2022
DOI: 10.3389/fpsyg.2022.879259
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance of the Bergen Social Media Addiction Scale Across Genders

Abstract: Social media addiction has been a hot issue in scientific research in recent years, its antecedents and consequences have been extensively studied. Among these studies, Bergen Social Media Addiction Scale (BSMAS) is one of the most commonly used instruments. However, little is known about whether this scale has the equivalent psychometric properties for men and women. The purpose of the current study is to examine the measurement invariance (including configural invariance, metric invariance, scalar invariance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
0
12
0
5
Order By: Relevance
“…We used the Bergen Social Media Addiction Scale (BSMAS) to assess PSMU, which has gained strong validity in the Chinese population [ 30 , 31 ]. BSMAS is designed based on the components of addiction theory.…”
Section: Methodsmentioning
confidence: 99%
“…We used the Bergen Social Media Addiction Scale (BSMAS) to assess PSMU, which has gained strong validity in the Chinese population [ 30 , 31 ]. BSMAS is designed based on the components of addiction theory.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement invariance testing is often performed through an iterative process. A series of increasingly restrictive confirmatory factor analytic (CFA) models determine the extent to which measurement parameters (loadings and intercepts) are equivalent across different samples or time points [ 40 , 45 , 46 ]. Associations between manifest indicators and latent constructs, such as regression intercepts, factor loadings and residual (error/uniqueness) variances, are involved.…”
Section: Introductionmentioning
confidence: 99%
“…The above controversy has arisen due to the assumption that "the measurement and the structure of the underlying construct are equivalent across groups" [39][40][41] and the failure to perform SAS-SV invariance tests. It remains unclear whether the functions of SAS-SV are identical across male and female participants, and thus, verification of the lack of cross-gender measurement bias is required.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most widely used internationally are the Bergen Social Media Addiction Scale (BSMAS) and the 9-item Internet Gaming Disorder Scale-Short Form (IGDS9-SF) both of which have been used among various populations including young adults. [15][16][17][18] The BSMAS has been shown to be an effective tool to assess the risk of SMA among Korean young adults with a good testretest reliability at a three-week interval (r=0.75) and very good internal consistency (Cronbach's α=0.86) as well as showing satisfactory convergent validity. 15 It has also been shown to be a valid instrument for assessing SMA risk among Mongolian university students.…”
Section: Introductionmentioning
confidence: 99%
“…15 It has also been shown to be a valid instrument for assessing SMA risk among Mongolian university students. 16 Examples using IGDS9-SF include a largescale study among 2,363 Iranian adolescents, which showed that the IGDS9-SF has robust psychometric properties as evidenced in its internal consistency, construct validity, criteriarelated validity, concurrent validity, and minimum floor and ceiling effects. 17 Another better example is a recently published systematic review on the psychometric properties of the IGDS9-SF showing its significant psychometric advantages.…”
Section: Introductionmentioning
confidence: 99%